How Can Legal Education Speak to the Discovery-enriched Curriculum?. (January 2017) - Pascoe, Daniel
City University of Hong Kong's (CityU) Discovery-enriched Curriculum (DEC) is a pedagogical approach involving discovery, innovation and creativity. With its focus on invention and experimentation, this approach lends itself naturally to the artistic and science-based disciplines; yet with an open mind, it can also be implemented within the undergraduate curriculum in law. This article discusses the DEC and its theoretical basis within the educational literature on discovery-based learning and the undergraduate research movement, before moving on to suggest the ways and means by which the undergraduate law curriculum at CityU could be changed in order to implement DEC and equally as importantly the ways in which established law-teaching practices already fit within the DEC framework. To fully implement DEC within CityU's Bachelor of Laws curriculum, some changes to long-standing teaching practices and the list of core courses will be necessary, but perhaps fewer changes than a sceptic might first believe. Overall, DEC has the potential to become a model for other law schools to follow in adopting inductive learning methods, if these are implemented in accordance with the results of existing pedagogical research.